Salafi’s Textualism in Understanding Qur’an and Hadith - Kiki Adnan Muzakki (Qur'an and Hadith Academic Society, 2019)
This paper discusses salafi’s textualism in understanding Quran and Hadith, especially the early salafi’s figures who have great influence in the theology of salafi. Literature study method by examining the books and biographies related to the topic is used in this paper. According to salafi everything that is not mentioned clearly in Quran and Hadith should not be done, and must be left and kept away. Aḥmad Ibn Ḥanbal which is considered as the inventor of salafi strongly refused Mu’tazilah doctrine who said that Quran is a creature in al-Ma’mun era, because this thought is not exist in Quran and Hadith then the successor of salafi thought Ibnu Taimiyah did not accept the interpretation of Allah attribute, he accepted the ayah and hadith about attribute textually.